Plasma fuelling with cryogenic pellets in the stellarator TJ-II. (4th April 2017) - McCarthy, K.J.; Panadero, N.; Velasco, J.L.; Combs, S.K.; Caughman, J.B.O.; Fontdecaba, J.M.; Foust, C.; García, R.; Hernández Sánchez, J.; Navarro, M.; Pastor, I.; Soleto, A.
Abstract: Cryogenic pellet injection is a widely used technique for delivering fuel to the core of magnetically confined plasmas. Indeed, such systems are currently functioning on many tokamak, reversed field pinch and stellarator devices. A pipe-gun-type pellet injector is now operated on the TJ-II, a low-magnetic shear stellarator of the heliac type. Cryogenic hydrogen pellets, containing between 3 × 10 18 and 4 × 10 19 atoms, are injected at velocities between 800 and 1200 m s −1 from its low-field side into plasmas created and/or maintained in this device by electron cyclotron resonance and/or neutral beam injection heating. In this paper, the first systematic study of pellet ablation, particle deposition and fuelling efficiency is presented for TJ-II. From this, light-emission profiles from ablating pellets are found to be in reasonable agreement with simulated pellet ablation profiles (created using a neutral gas shielding-based code) for both heating scenarios. In addition, radial offsets between recorded light-emission profiles and particle deposition profiles provide evidence for rapid outward drifting of ablated material that leads to pellet particle loss from the plasma. Finally, fuelling efficiencies are documented for a range of target plasma densities ( 4 × 10 18 – 2 × 10 19 m −3 ). These range from 20%– 85% and are determined to be sensitive to pellet penetration depth. Additional observations, such as enhanced core ablation, are discussed and planned future work is outlined.